The Relationship Between The Use of Indirect Language Learning Strategies and Chinese Language Achievement in Reading and Writing Among Students in Years 7 To 10 At Ascot International School In Bangkok, Thailand - Xiao, Han; Lynch, Richard (Scholar: Human Sciences, 2017)
This study aimed to examine the use of indirect language learning strategies and the relationship between those strategies and Chinese academic achievement of year 7 to year 10 students who are learning Chinese as a foreign language at Ascot International School in Bangkok, Thailand. The study followed a quantitative research methodology utilizing two research instruments: the questionnaire of indirect learning strategies for Chinese learning and the unit quizzes of the IGCSE (International General Certificate of Secondary Education) Chinese course. The study was carried out during the second term of academic year 2015-2016 with 91 respondents. The use of indirect learning strategies focused on the use of metacognitive, affective and social language strategies. The Chinese achievement focused on reading and writing achievement. The study resulted in the following main findings. Year 7 to year 10 students used at a high level both metacognitive and social strategies for their Chinese learning. They used affective strategies at a medium level. Also, the use of overall indirect learning strategies was medium. There was a positive significant relationship between the use of metacognitive strategies and Chinese achievement. There was no significant relationship between affective strategies and Chinese achievement. There was a positive significant relationship between the use of social strategies and Chinese achievement. There was a positive significant relationship found between the use of overall indirect learning strategies and Chinese achievement as well. Recommendations for Chinese teachers, students and future researchers are also provided in this study.